Piglet named Mercy - DiCamillo, Kate; Van Dusen, Chris (Somerville, Massachusetts Candlewick Press, 2019)
When a pig named Mercy arrives at the Watsons' front door, she brings love and chaos to their lives.
106900
Keywords: Swine -- Juvenile fiction; Pigs -- Fiction; Piglets -- Juvenile fiction; Juvenile Fiction -- Animals -- Pigs; Picture books for children